Analisis Pengaruh Variasi Suhu Pembakaran Terhadap Mikrostruktur Dan Kandungan Silika Abu Kulit Kakao (Theobroma Cacao) Dengan Metode SEM Dan XRD - Daulay, Abdul Halim; Masthura; Pratiwi, Arninda (JFT: Jurnal Fisika dan Terapannya, 2022)
This study aims to determine the effect of combustion temperature on the microstructure and particle diameter of the average silica ash of cocoa shells, and to determine the effect of combustion temperature on the silica content of cocoa shell ash. The method used is experimental through a quantitative approach. The basic material used is cocoa husk (Theobroma cacao) with combustion temperatures of 450, 550, 650, and 750 oC. The tests used to determine the microstructure and silica content of cocoa husk ash were SEM and XRD after which they were analyzed again using Digimizer Software and X-Powder Software. SEM results based on microstructure indicate the occurrence of agglomeration in the cocoa ash silica sample, and it is known that the particle diameter size of sample A = 1,6916 µm, sample B = 0,7824 µm, sample C = 0,7809 µm, and sample D = 0,7173 µm. Based on the XRD results, it can be seen that the silica contained in sample A = 34,8%, sample B = 49,0%, sample C = 65,0%, and sample D = 70,6%. Based on the SEM results, the best results are in the sample which has the smallest size, namely sample D with a particle diameter of 0,7173 µm and based on XRD results the best results are in sample D with the highest SiO2 content of 70,6%. So that the combustion temperature affects the results of SEM and XRD where the effective temperature in the manufacture of cocoa shell ash silica is 750 oC.